Canali, Mauro. The Matteotti Murder and Mussolini. The Anatomy of a Fascist Crime (Ruth Ben-Ghiat, Foreword; Ann. T. Pichey, trans). Palgrave MacMillan, 2024, 272 pp. ISBN 9783031414701 - Abreu Colombri, José Antonio (Atenea (Concepción), 2024)
Mauro Canali’s work is the result of a long cycle of sorting out sources on the fascist system and Mussolini’s political career. This editorial project took shape in the months leading up to the centenary of the crime against the multitalented Giacomo Matteotti through the assembly of various academic papers and publications in Italian. From a long list, by thematic spe- cialization, the following works stand out: La scoperta dell’Italia. Il fascismo raccontato dai corrispondenti americani, published in Venice (2017), and Il delitto Matteotti, revised and republished in Bologna (2024). The different chapters of The Matteotti Murder and Mussolini. The Anatomy of a Fascist Crime are grouped into four thematic blocks: “Anatomy of a Policital Crime,” “Mussolini´s Responsabilities,” “Mussolini´s Defenders” and “After.” The analytical models focus on the study of public administration documents and journalistic publications about a crime that acquired a strong international resonance and shocked large sectors of Italian society.